A meta-analysis of the traditional herb Zicao and its active components for atopic dermatitis - Wu, Qin-yao; Jiang, Ya-yi; Ming, Jun-e; Hao, Ping-sheng (Frontiers in Pharmacology, 2026)
BackgroundThe traditional Chinese herb Zicao and its bioactive constituents demonstrate therapeutic potential for atopic dermatitis (AD), and a systematic review assessing its effectiveness for managing AD is still lacking.PurposeThis meta-analysis aimed to synthesize the effects of Zicao on AD animal models and elucidate the underlying mechanisms.MethodsTen databases (PubMed, Embase, Cochrane, Web of Science, China National Knowledge Internet (CNKI), VIP, CBM, Wanfang, Google Scholar, and ProQuest Dissertations & Theses Global) were systematically searched from the inception through May 2025. Study quality was assessed using SYRCLE’s risk-of-bias tool. Random-effects models pooled standardized mean differences (SMDs) with 95% confidence intervals (CIs) for primary outcomes (dermatitis severity and scratching behavior) and secondary outcomes (cytokines, epidermal thickness, and filaggrin (FLG)). Subgroup analyses examined the animal species, modeling method, drug formulation, and intervention protocol. Publication bias was evaluated via funnel plots and Egger’s regression; sensitivity analyses utilized the leave-one-out methodology. Analyses were conducted in R version 4.3.2 software.ResultsTen studies (n = 316 animals) revealed the following: Zicao treatment significantly decreased the severity of dermatitis (SMD = −3.30, 95% CI: −4.37 to −2.23; p < 0.001) and scratching behavior (SMD = −2.60, 95% CI: −3.76 to −1.44; p < 0.01). In addition, Zicao treatment significantly decreased cytokines: TNF-α, thymic stromal lymphopoietin (TSLP), IL-4, IL-13, IgE, and mast cell infiltration, whereas no significant effects were observed for IFN-γ, IL-6, epidermal thickness, or FLG expression.ConclusionThe traditional Chinese herb Zicao ameliorates AD symptoms and Th2-associated inflammation but exhibits limited efficacy in epidermal barrier restoration. However, the pooled effect estimates from this meta-analysis must be interpreted with caution as the preliminary indications of potential efficacy rather than as conclusive evidence, given the widespread methodological limitations and the absence of pharmacokinetic and toxicological data in the included studies. Therefore, future investigations using chemically standardized preparations and comprehensive safety assessments are needed to validate these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023449172.